Racial/ethnic and gender disparities of the impact of the COVID-19 pandemic in out-of-hospital cardiac arrest (OHCA) in Texas. (October 2022) - Chavez, Summer; Huebinger, Ryan; Chan, Hei Kit; Schulz, Kevin; Panczyk, Micah; Villa, Normandy; Johnson, Renee; Greenberg, Robert; Vithalani, Veer; Al-Araji, Rabab; Bobrow, Bentley
Abstract: Introduction: Prior research shows a greater disease burden, lower BCPR rates, and worse outcomes in Black and Hispanic patients after OHCA. Female OHCA patients have lower rates of BCPR compared to men and other survival outcomes vary. The influence of the COVID-19 pandemic on OHCA incidence and outcomes in different health disparity populations is unknown. Methods: We used data from the Texas Cardiac Arrest Registry to Enhance Survival (CARES). We determined the association of both prehospital characteristics and survival outcomes with the pandemic period in each study group through Pearson's χ 2 test or Fisher's exact tests. We created mixed multivariable logistic regression models to compare odds of cardiac arrest care and outcomes between 2019 and 2020 for the study groups. Results: Black OHCA patients (aOR = 0.73; 95% CI: 0.65 – 0.82) had significantly lower odds of BCPR compared to White OHCA patients, were less likely to achieve ROSC (aOR = 0.86; 95% CI: 0.74 – 0.99) or have a good CPC score (aOR = 0.47; 95% CI: 0.29 – 0.75). Compared to White patients with OHCA, Hispanic persons were less likely to have a field TOR (aOR = 0.86; 95% CI: 0.75 – 0.99) or receive BCPR (aOR = 0.78; 95% CI: 0.69 – 0.87). Female OHCA patients had higher odds of surviving to hospital admission compared to males (aOR = 1.29; 95% CI: 1.15 – 1.44). Conclusion: Many OHCA outcomes worsened for Black and Hispanic patients. While some aspects of care worsened for women, their odds of survival improved compared to males.